Perancangan Ergonomis Stasiun Kerja untuk Meningkatkan Produktivitas Proses Pemotongan pada Produksi UV Harness di PT FMS - Setiyawan, Agus; Firman Ardiansyah Ekoanindiyo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
One key factor influencing efficiency is the application of ergonomic principles, particularly physical ergonomics, which includes aspects of anthropometry and repetitive motion. This study was conducted at PT FMS, a manufacturer of UV Harnesses, focusing on the cutting workstation that still heavily relies on manual labor. With a targeted productivity increase of 135% and no significant change in the production plan, the standing work posture maintained throughout the day poses a risk of fatigue and potential injury to operators. This study aims to analyze and propose improvements to reduce fatigue and design an ergonomic cutting workstation. Anthropometric data were used to calculate percentiles for designing an ergonomic worktable, while body discomfort and movement-related injury risks were assessed using the Nordic Body Map (NBM) and Rapid Entire Body Assessment (REBA) methods, respectively. The analysis revealed that the non-ergonomic workstation design caused physical complaints such as back and leg pain, indicating the need for redesign. It is recommended that the company routinely evaluate ergonomic factors and regularly distribute NBM questionnaires to all production operators to identify potentially harmful work activities.